The influence of brand image and promotion on customer loyalty - Ridwan Nasution (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2025)
Brand image and promotion are factors that can be considered by consumers in decision making. This research method uses a quantitative approach. The sample of this research is customers at Mie Atok Rantauprapat. The results of the study show that brand image and promotion affect customer loyalty.